Study guides

Q: (4a-5) plus (3a plus 6)

Write your answer...

Submit

Related questions

Yes. 3a plus 12 plus 6 is an example of an Equation.

No. 3a 12 plus a 6 is not a solution Of an equation.

If a + b = 6, what is the value of 3a + 3b?

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

6-3a**2+7+4a-5a+18 3a**2-1a+31

5a + 11

12

= a + b - 2

6a + 8 = 2(3a + 4)

Subtract 6 from each side: 3a = -14 Divide each side by 3: a = -14/3 ie = Minus four and two thirds

(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3

3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28

0.5

a + b - 2 is the answer in simplest terms. without telling us what a or b is this is the most accurate answer.

a+7/3 = 6 Multiply all terms by 3:- 3a+7 =18 3a = 18-7 3a = 11 a = 3 and 2/3

Subtract 6 from each side: 3a = 9Divide each side by 3: a = 3Job done.

Yes.

15 ac + 20 bc + 6 ad + 8 bd =3a (5c + 2d) + 4b (5c + 2d) =(3a + 4b) (5c + 2d)

6

3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.

3 times 6 is 18 2 times 5 is 10 18 plus 10 is 28

Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6

No they are not equivalent, commutative property applies to addition, not subtraction. The two expressions will be equal only if a = 2, in which case you will have 6-6 = 6-6 = 0

4a + 1 - a =19, rewrite your question, 4a + -a + 1 =19, 3a + 1 =19, subtract 1 from each side 3a = 18, divide by 3, a =6

a-1<2a-6<9+3a